Mediating effect of self-esteem and religiosity in the relationship between stress, peer substance use, depression and drug abuse among adolescents in Somolu, Lagos, Nigeria - Uzodinma, Uba Ikechukwu (2013)
The present study examined the mediating effect of self-esteem and religiosity in the relationship between stress, peer substance use, depression and drug abuse in Somolu, Lagos, Nigeria, given the high drug abuse cases reported in the zone. Three hundred and fifty two adolescents aged 13 to 18years (M=15.48, SD=1.53) participated in the study. The two theories (Bandura, 1977; Stryker, 1980) used in the present study highlighted two main assumptions. First, adolescents with high selfesteem can overcome stress, peer substance use and depression in relation to drug abuse. Second, adolescents with high levels of religiosity can also triumph over stress, peer substance use and depression in relation to drug abuse. Respondents were identified using multi-stage cluster sampling. The data was analyzed using descriptive statistics, t-test, ANOVA, Pearson correlation and regression analysis. Drug Abuse Screening Test (DAST: Skinner, 1982) was used to assess drug abuse. Perceived Stress Scale (PSS) by Cohen (1983) was used to measure stress. Peer substance use sub-scale of the Communities that Care Youth Survey developed by Hawkins et al. (1992) was used to measure peer substance use. Beck Depression Inventory (BDI II) by Beck, Gregory and Steer (1996) was used to measure depression. Self-esteem was measured with the Rosenberg Self-Esteem Scale (Rosenberg, 1965), while Religiosity was measured with the Religious Background and Behaviors Questionnaire (RBB: Connors, Tonigan & Miller, 1996). The findings revealed that 36.9% (n = 130) of the adolescents in the study were substantial drug abusers, while 27% (95) were severe drug abusers. The results also indicated significant relationships among the main variables of the study (selfesteem,religiosity, stress, peer substance use, depression and drug abuse). Controlling for age and gender in the study, self-esteem appeared as the strongest unique predictor of drug abuse (Beta = -.407, p <.05) among adolescents, followed by peer substance use (Beta = .317, p <.05). The study also highlighted that selfesteem and religiosity are partial mediators of stress, peer substance use and depression in relation to drug abuse among respondents. The results emanating from the present study lend support to the theories of Bandura (1977) and Stryker (1980) by emphasizing the partial mediation potential of self-esteem and religiosity in the relationship between stress, peer substance use, depression and drug abuse. Future research may broaden these early findings, to help achieve a clearer and comprehensive depiction of these relationships.